Study of the effect of severity of maternal anemia on pregnancy outcome - بلال ديانا; عصام الدالي; لينا رمضان (Latakia University Journal -Medical Sciences Series, 2023)
· Aim of the study: To determine the effect of maternal anemia severity on maternal morbidity during the perinatal period. Patients and methods: A cross-sectional study of the type (case - control study design) was conducted and all admitted women in Tishreen University Hospital were followed up during the period between January 2019 and January 2021. The sample included 857 patients who met the inclusion criteria, and were divided into two groups according to the hemoglobin value (threshold 11 g / dl). The woman’s condition was followed up and recorded obstetric complications were monitored until delivery. The focus was on early labor, bleeding and pre-eclampsia. The relationship of anemia with the mother’s age, educational status, obstetric status and its relationship with health care during pregnancy and intake of Preventive iron, and after collecting data and conducting a complete study, the results were summarized according to tables showing the relationship between the variable. Results: The average age of the research sample patients was 26 ± 5.2 years. The prevalence rate of anemia was 53.9% of the study sample, and severe anemia reached 6.4%. We noticed that there were statistically significant differences between the incidence of anemia and age, with p-value = 0.001, where we find that the highest percentage of anemia, especially the severe degree, was among the first and last age groups (<20 and ≥40). We did not find a relationship between the incidence of anemia and educational level. We had statistically significant differences between the incidence of anemia and the obstetric condition with a p-value = 0.02, where anemia in general was more common among breech women (59%), and severe anemia was seen in a greater percentage among multiparents (25%).There were statistically significant differences between the occurrence of anemia and the number of health care visits with p-value = 0.01, where the percentage and severity of anemia decreased with the increase in the number of visits (from 77.2% in the absence of care visits to the clinic to 50.3% in the presence of <3 visits) Also, the percentage of anemia decreased with the preventive oral iron intake, with no cases of severe anemia being recorded when taking it regularly.With regard to pregnancy complications, premature delivery occurred in 10.9% of severe anemia cases, and inertia bleeding and transfusion of blood and its derivatives were higher with the presence of statistically significant differences with regard to blood transfusion with p-value = 0.003. As for premature labor and pre-eclampsia, And fetal death in the womb, it was more frequent in the anemia group compared to the control group, but without statistically significant differences, and in particular it was higher in the severe anemia group. Conclusion: There is a relationship between anemia and the age of the mother and the obstetric condition (the prevalence was higher among the breech and more severe among the multiparents), as well as with health care visits and preventive oral iron intake. The increase in the severity of anemia was also associated with an increase in the percentage of pregnancy complications in the mother (early labor, inertia bleeding, transfusion of blood and blood products, pre-eclampsia, fetal death in the womb).